A statistically analysis to determine the use of renewable sources for campus lighting, case study of technical faculty of Kosova - Bylykbashi, Blerina; Abdullahu, Fitore; Hoxha, Bukurije (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Considering the ever-increasing demand for electricity and the current crisis in this sector, various ways of generating electricity have been studied. Most of them are based on hybrid technologies as a solution to replace the relevant resources during the absence. In Kosovo, as an economically poor country, such technologies are rarely used. Public lighting in some countries is still considered unaffordable due to high cost. This study further demonstrates an environmentally friendly option for power generation using hybrid PV and Wind systems. The current study presents the study that was carried out on the campus of the technical faculty in Pristina. The analysis has been done analytically, which has resulted in the need for 6 hybrid lighting systems to achieve a coverage of the lighting needs, which so far lacks lighting in this part of the campus. A total of 461,448 kWh can be generated during the year from the wind turbine system and 796.11 kWh from the solar photovoltaic system. Considering that we have an ever-decreasing cost of such devices and from the analysis done it results that these systems are cost effective and ideal solutions for such cases and similar needs which are vital needs today.